While the dust is settling in New Zealand - Omer, Spahic (IslamiCity, 2019)
While the dust is settling in the aftermath of shootings at two mosques in New Zealand, some rather bigger and more consequential truths and dimensions start emerging. Undoubtedly, the killed brothers and sisters are global heroes. They are also martyrs and Jannah (Paradise)-bound (Insha’Allah we most sincerely hope and pray for them).